CLICKBAIT IN BEAUTY CONTENT: TYPES AND RELEVANCE OF HEADLINES IN ONLINE MEDIA - Daulay, Alya Salsabila; Nurmeilida , Nurmeilida; Regar , Rahmizul Ummi Br.; Batubara , Yohana Aulia; Natsir , M. (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
The rise of digital media has intensified the use of clickbait as a strategy to capture readers' attention and boost engagement. This study analyzes the types and relevance of clickbait in 15 beauty-related articles from various online platforms using a descriptive qualitative method and Barthes' semiotics theory. The findings reveal that teasing clickbait is the most commonly employed type, accounting for 40% of the analyzed headlines. Exaggeration and formatting clickbait follow with 26.7% and 20%, respectively, while less common types include ambiguous and inflammatory clickbait, each at 6.7%. Graphic, bait-and-switch, and wrong clickbait were not observed in the sample. While these strategies effectively attract attention, they often risk creating a mismatch between the headline and the actual content, leading to concerns about audience trust and ethical implications. This research contributes to the discourse on digital media practices by emphasizing the importance of balancing engaging headlines with accurate and relevant content in beauty journal